Intracerebroventricular administration of Shiga toxin type 2 induces striatal neuronal death and glial alterations: an ultraestructural study - Goldstein Raij, Jorge (2007)
Shiga toxin (Stx) from enterohemorrhagic Escherichia coli (STEC) is the main cause of hemorrhagic colitis which may derive to hemolytic–uremic syndrome (HUS). HUS is characterized by acute renal failure, thrombocytopenia and microangiopathic hemolytic anemia. Mortality in the acute stage has been lower than 5% of total affected argentine children with endemic HUS. Common signs of severe CNS involvement leading to death included seizures, alteration of consciousness, hemiparesis, visual disturbances, and brainstem symptoms. The main purpose of the present work was to study the direct involvement of Stx2 in brain cells by intracerebroventricular (i.c.v.) administration of Stx2. Immunodetection of Stx2 was confirmed by immunoelectron cytochemistry in different subsets and compartments of affected caudate putamen cells of corpus striatum. Transmission electron microscopy (TEM) studies revealed apoptotic neurons, glial ultrastructural alterations and demyelinated fibers. The i.c.v. microinfusion was applied for the first time in rats to demonstrate the direct action of Stx2 in neurons and glial cells. The toxin may affect brain neuroglial cells without the involvement of proinflammatory or systemic neurotoxic elements.